A Critical Evaluation of the Political Dynamics of the Post-1991 Ethiopian-Eritrean Relations: Security Implications for the Greater Horn & Sahel Regions - Jalu, Abebe Tigire; Simuziya, Nsama Jonathan (Вісник гуманітарних наук, 2025)
After a protracted conflict from 1962 to 1991, Eritrea finally won its de facto independence in 1991 and got de jure independence via a referendum in 1993, effectively splitting from Ethiopia. From 1991 to 1998, the two countries maintained cordial relations until another war between them broke out in 1998. Relations continued to be strained from 1998 to 2018, and during this period, Eritrea remained one of Ethiopia’s troubling security challenges in foreign policy endeavors. Unlike other neighbors within the Greater Horn of Africa, Ethiopia and Eritrea have had a complex relationship, that is, one of unity and separation, war and peace, hate and love, cooperation and competition. However, in 2018, a historic peace deal was signed between the two states, where they pledged to ‘bury their past’ and bring a new dawn to their relations. In 2020, Eritrea joined the Ethiopian government’s side in the Tigray Conflict, further strengthening the alliance. But how the Tigray conflict concluded in 2022 strained their relations. This was aggravated by the signing of the Memorandum of Understanding (MoU) between Ethiopia and Somaliland. The MoU is part of Ethiopia’s aim to get access to the sea and become a naval power, which has raised concern because it has bypassed Somalia and signed a deal with a territory that Somalia considers to be under its jurisdiction. Furthermore, Somaliland is not recognized as a state by key organizations such as the African Union (AU), the United Nations (UN), the European Union (EU), and the Arab League. Therefore, such a brazen move of disregarding the sovereignty of Somalia has, understandably, increased Eritrea’s suspicion that there might be more ominous political motives at play than meets the eye. This is because Eritrea and its ports were part of Ethiopia for around three decades, and Ethiopia’s concentration on acquiring a ’breathing space’ raised the prospect of reclaiming Eritrean ports. Consequently, Eritrea, Somalia, and Egypt collaborated by signing an agreement accentuating the right to protect neighbors’ sovereignty. This tripartite treaty works as a form of hedging or buffer against an increasingly assertive Ethiopia. While a full-scale conflict between Ethiopia and Eritrea is unlikely, the implications of their weakening relations could cause considerable spillover security effects beyond the region. These security challenges could potentially create an opportune environment for various rebel groups, including jihadists, to reassert themselves. For instance, the current conflict in Sudan, where two rival army factions are jostling for power, implies that both camps are soliciting and receiving support from various interested actors within and outside the region. This situation provides an avenue for potential proxy wars to ensue because volatile environments only work to strengthen rebel networks, as dissidents thrive mainly in weak and conflict-ridden states. In the current Ethiopian Eritrean standoff, the Sudanese crisis is a significant variable to consider because Sudan is surrounded by prime arms-trafficking Sahel hubs, where weapons are smuggled through Libya, Chad, and the Central African Republic. Thus, the fundamental goal of this study is to critically analyze (especially) the post-2018 Ethiopian-Eritrean relations and gauge their tenability through a neoclassical realism theoretical lens. The findings suggest that due to competing interests by various domestic, regional and international actors in the Horn of Africa, coupled with the covert activities of rebel factions in the Sahel, the Ethiopian- Eritrean relations will continue to be precarious and may only be regulated by the change of the regime or by the balance of power politics. Data for this study were gathered through content analysis of literature, digital ethnography, and online sources.